Deteksi Deformasi Vertikal Permukaan Jembatan Mulya Agung Tahun 2021 – 2022 Menggunakan Data Mobile Laser Scanner - Wulan Ratna Mayangsari; Andaru, Ruli (Journal of Geospatial Science and Technology, 2025)
The Terbanggi Besar - Pematang Panggang - Kayu Agung Toll Road (TBPPKA) is a part of the Trans-Sumatra Toll Road (JTTS) that has been operational since November 2019, necessitating road maintenance. Routine maintenance is carried out on all toll road assets, including the Mulya Agung Underpass Bridge on the TBPPKA Toll Road at KM 240+822. This study aims to analyze vertical deformations on the bridge's surface using Mobile Laser Scanner (MLS) as a step in bridge monitoring and maintenance efforts. MLS technology was chosen for its capability in fast and accurate scanning, making it effective for multi-epoch measurements. Data generated from the MLS measurements come in the form of a point cloud, which still needs to be registered using the Iterative Closest Point (ICP) method to ensure the data is in the same coordinate system. Based on the research results, the RMS accuracy value in the registration process is 0.021 meters out of a total of 596,963 points sampled. To determine the presence of vertical deformation, a significant test was conducted using the Student's t-test. Based on the significant test results with a 95% confidence level, the calculated t-value (2.705) was found to be greater than the tabulated t-value (2.010), indicating a significant change in elevation. The maximum elevation increase is 9.1 cm on the south side of the bridge, while the minimum decrease is -3.4 cm on the north side of the bridge. Vertical deformations occur at the end of the bridge connected to the road, which is attributed to repairs involving asphalt addition. The MLS method has proven to be effective in detecting vertical deformations on the bridge with a level of detection of 2 cm.